Maternal positive coparenting and adolescent ego-identity: the chain mediating role of fathers’ marital satisfaction and adolescent peer relationships - Ji, Wanghua; Lan, Rui Ming; Ma, Peng; Zhang, Hongpo; Fan, Lijun (Frontiers in Psychology, 2023)
Introduction Based on the ecological systems theory and the family systems theory, this study explores the mechanisms underlying the effects of maternal positive coparenting on adolescent ego-identity. Methods This study employed the Maternal Positive Coparenting Scale to assess mothers, the Father Marital Satisfaction Scale to examine fathers, and the Adolescent Peer Relationship Scale, along with the Ego-Identity Scale, to evaluate adolescents. This comprehensive approach involved investigating 522 families, encompassing both parents and adolescents. Results The results obtained indicate a significant positive correlation between maternal positive coparenting and adolescent ego-identity. Peer relationships mediated the relationship between maternal positive coparenting and adolescent ego-identity. Father marital satisfaction mediated the relationship between maternal positive coparenting and adolescent ego-identity insignificantly. Paternal marital satisfaction and adolescent peer relationship have a chain mediating role between maternal positive coparenting and adolescent ego-identity. The study contributes by offering insights from the perspectives of family and peer relationships for further enhancing the development of adolescent ego-identity.